2012
DOI: 10.1007/128_2012_340
|View full text |Cite
|
Sign up to set email alerts
|

A Perspective on Dietary Phytochemicals and Cancer Chemoprevention: Oxidative Stress, Nrf2, and Epigenomics

Abstract: Oxidative stress is caused by an imbalance of reactive oxygen species (ROS)/reactive nitrogen species (RNS) and the antioxidative stress defense systems in cells. ROS/RNS or carcinogen metabolites can attack intracellular proteins, lipids, and nucleic acids, which can result in genetic mutations, carcinogenesis, and other diseases. Nrf2 plays a critical role in the regulation of many antioxidative stress/antioxidant and detoxification enzyme genes, such as glutathione Stransferases (GSTs), NAD(P)H:quinone oxid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
80
0
2

Year Published

2014
2014
2017
2017

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 120 publications
(87 citation statements)
references
References 248 publications
(276 reference statements)
5
80
0
2
Order By: Relevance
“…The transcriptional activation of antioxidant and detoxification genes is increased by Nrf2 through its interaction with AREs (34), and accumulating evidence indicates that dietary phytochemicals with chemopreventive potential could enhance the activities of antioxidant and detoxification enzymes via the Nrf2 pathway (35). This study shows that SFN increased HO-1, NQO1, and UGT1A1 mRNA and protein levels as well as the nuclear translocation and expression of total endogenous Nrf2 protein in JB6 Pþ cells (Fig.…”
Section: Discussionsupporting
confidence: 53%
“…The transcriptional activation of antioxidant and detoxification genes is increased by Nrf2 through its interaction with AREs (34), and accumulating evidence indicates that dietary phytochemicals with chemopreventive potential could enhance the activities of antioxidant and detoxification enzymes via the Nrf2 pathway (35). This study shows that SFN increased HO-1, NQO1, and UGT1A1 mRNA and protein levels as well as the nuclear translocation and expression of total endogenous Nrf2 protein in JB6 Pþ cells (Fig.…”
Section: Discussionsupporting
confidence: 53%
“…Once the interaction of Keap1 and Nrf2 is disrupted and cytoplasmic and nuclear Nrf2 accumulates, Nrf2 binds to the ARE in the promoter region of some phase II enzyme genes and triggers the expression of Nrf2 downstream enzymes (59)(60)(61). Therefore, many dietary phytochemicals with chemopreventive potential have been reported to enhance the activities of phase II enzymes through the Nrf2-ARE pathway (20). Interestingly, the results of this study showed reserpineinduced ARE-luciferase activity in HepG2-C8 cells (Fig.…”
Section: Discussionmentioning
confidence: 64%
“…In addition, we recently demonstrated that Nrf2 is downregulated during 12-Otetradecanoylphorbol-13-acetate (TPA)-induced neoplastic transformation of mouse skin epidermis JB6 P+ cells (18). The deregulation of the antioxidant defense system has received increased attention because this complication promotes susceptibility and neoplastic progression (18)(19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, NRF2 activity is restored by phytochemicals that reduce methylation of CG islands (297). With regard to oxidative stress, AD patients display high homocysteine and low vitamin B 12 and folate levels in blood, suggesting a dysregulation of the S-adenosyl methionine cycle that is required for DNA methylation (275).…”
Section: Ros Control the Nrf2 Through Redox Modification Ofmentioning
confidence: 99%